Maternal nutrition during early and late gestation in gilts and sows under commercial conditions: impacts on maternal growth and litter traits() - Mallmann, André L (J Anim Sci, 2019)
The effects of two different feeding levels, offered in two phases during gestation, on body measurements and litter traits were evaluated in 152 gilts and 551 sows. The treatments consisted of the combination of two gestation phases (phase 1—days 22 to 42; phase 2—days 90 to 110) and two feed amounts (1.8 or 3.5 kg/d). Females were weighed on days 22, 42, 90, and 110 of gestation. Born alive and stillborn piglets were weighed within 12 h of birth. Total placental efficiency (ratio between litter weight and total placental weight) was measured in 518 females. Variables concerning body measurements at days 42 and 90 of gestation were analyzed considering the effects of feed amount, parity order (PO) and its interaction as a 2 × 2 factorial arrangement. Body measurements at day 110 of gestation and litter traits were analyzed considering the effects of feed amounts in phase 1, feed amounts in phase 2, PO and their interactions, as a 2 × 2 × 2 factorial arrangement. As expected, BW, backfat, and caliper units were greater at days 42, 90, and 110 (P ≤ 0.006) for females fed 3.5 kg/d during the previous phase than those fed 1.8 kg. No differences were observed among feed levels in total number of piglets born, mummified fetuses, sum of born alive and stillborn piglets, and within-litter birth weight CV (P ≥ 0.118). The percentage of stillborn piglets was affected by a three-way interaction (feed level at phase 1 × feed level at phase 2 × PO). Gilts fed 1.8 kg/d at phase 1 and 3.5 kg/d at phase 2 had fewer stillborn piglets than the other females (P ≤ 0.004). Birth weight was not affected by feed levels (P ≥ 0.153); however, sows had heavier piglets than gilts (P < 0.001). Females fed 3.5 kg/d during phase 2 tended to have heavier litters (P = 0.054) than those fed 1.8 kg/d. Feeding a high level at phase 2 reduced the occurrence of lightweight piglets in gilts, but not in sows (feed level phase 2 × PO; P = 0.031). Total placental weight, average placental weight, and total placental efficiency were not affected by feed level at phase 1, feed level at phase 2 or interactions (P > 0.14). Sows had total placental weight and average placental weight greater (P ≤ 0.003) than gilts. In conclusion, increasing feed intake during phase 1, phase 2, or both phases resulted in increased maternal BW gain, without expressive effects on litter traits. Feeding 3.5 kg/d to gilts during phase 2 reduced the occurrence of lightweight piglets.